2003
DOI: 10.1115/1.1533059
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Assessment of Numerical Predictive Accuracy for Electronic Component Heat Transfer in Forced Convection—Part I: Experimental Methods and Numerical Modeling

Abstract: Numerical predictive accuracy is assessed for component-printed circuit board (PCB) heat transfer in forced convection using a computational fluid dynamics (CFD) software for the thermal analysis of electronic equipment. This is achieved by comparing numerical predictions with experimental benchmark data for three different components, mounted individually on single-component PCBs, and collectively on a multi-component PCB. Benchmark criteria are based on measured steady-state component junction temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Addressing this weakness, Rodgers et al [35,164] [169][170][171][172][173][174]. These studies have found CTM accuracy to be generally within 10% of the detailed component model predictions for both junction temperature and heat flows from the package external surfaces.…”
Section: Prediction Of Electronic Component Heat Transfermentioning
confidence: 99%
See 4 more Smart Citations
“…Addressing this weakness, Rodgers et al [35,164] [169][170][171][172][173][174]. These studies have found CTM accuracy to be generally within 10% of the detailed component model predictions for both junction temperature and heat flows from the package external surfaces.…”
Section: Prediction Of Electronic Component Heat Transfermentioning
confidence: 99%
“…The two-equation standard k-s model is subsequently used for refined sub-system analysis, such as for PCB assemblies. However, this strategy has been shown to fail to yield accurate predictions o f component operating temperature in air-cooled PCBs [35], as neither a laminar or standard high-Reynolds number k-s flow model are specific for such flows.…”
Section: Prediction Of Electronic Component Operational Temperaturementioning
confidence: 99%
See 3 more Smart Citations